(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In this article describes the concepts of terminology, terminology. Examples illustrate the typological study, classification and comparison of functional features of the terminological and lexical-semantic edges of medical linguistics of the present day. Modern medical terminology as a macro-terminological system is represented by a complex of rapidly developing medical and paramedical terms, formed as a result of the centuries-old development of World Medical Science.